The Cycle of Violence: Examining Attitudes Toward and Experiences of Corporal Punishment in a Representative German Sample - Witt, Andreas (Journal of interpersonal violence, 2021)
The use of corporal punishment (CP) is controversial despite the negative consequences of its use that have been documented. Consequences include the use of CP by those who experienced CP themselves, described in the theory of the cycle of violence. There are little data on the cycle of violence, especially on those who break it and in representative samples. This study examines the cycle of violence in a representative sample by analyzing experiences of and attitudes toward CP. Attitudes toward, and own experiences of, CP by their parents were assessed in a sample of 2,519 individuals (female 54.6%, age range = 14-99 years, M = 48.9 years). Latent class analysis (LCA) was used to identify subgroups of participants who support and oppose CP. Breaking the cycle, defined as having experienced CP and opposing CP, was examined. Factors associated with positive and negative attitudes toward CP were identified using group comparisons and binary logistic regression. The majority of the sample opposed CP (56%), whereas one third supported less severe forms of CP and 8.2% also supported severe CP. Those supporting CP reported having experienced CP by their parents more often. Of those who had experienced CP, 47% were identified as breaking the cycle. Female gender, younger age, not being divorced, and being married and living together, as well as a higher level of education were associated with breaking the cycle. Even though CP was legally banned in Germany, a relatively high proportion still reports positive attitudes toward and experiences of CP. The ban of CP by the federal government seems to be an effective measure to change attitudes on a societal level as rates were lower in comparison with earlier studies. Future studies should examine interactions between different types of CP, attitudes toward its use, and additional mediating factors.